Filsafat Dan Agama; Sebuah Kajian Kompromis-Analitis - Abd. Aziz (Institut Ilmu Keislaman Zainul Hasan Genggong, 2018)
According to Al-Farabi, philosophy is a knowledge of materiel and a way to investigate the real essence of universe. Whereas religion, according to J.G. Frazer, is a devotion to God who puts in order universe movement. When philosophy and religion are faced one and other, both of them are looked like something incompatible, even in factually they are completing each other. In order to have a better religion, someone needs to have his rationality in the way of understanding religion. And also, to control philosophy which is based on rationality, philosophy needs a religion guidance. Many people perceive that philosophy could not be in harmony with religion, since philosophy anchored its idea to the rationalistic-empiricism basics and religion based its idea to the transcendentally dalîlof Supra Causa. Therefore, Emile Durkheim said, religion was a mystical paradigm where rationality could not get into. So did Auguste Comte, he said people need a religion only when he had no ability to develop his rationality. Even contrary, does religion order people to always